1992
DOI: 10.2307/1940159
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Regulation, and the Determination of Abundance in an Insular Song Sparrow Population

Abstract: The population dynamics of the Song Sparrow, Melospiza melodia, were studied for 15 yr on Mandarte Island, in southwestern British Columbia, Canada. This population exhibited a high median density (7.8 females/ha) and fluctuated strongly (10—fold or more) from year to year. The population received few successful immigrants, even at low densities, and its dynamics were thus driven by local events. Two strong density—dependent regulating mechanisms were detected. First, reproductive output was strongly depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
176
2
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(191 citation statements)
references
References 49 publications
9
176
2
4
Order By: Relevance
“…Individuals are unlikely to remain passively assigned to poor habitat or status as long as there are no vacancies, as assumed by models of territorial species demography, or ideal despotic distribution (IDD; Fretwell & Lucas 1970). Instead, they may attempt to improve their breeding career actively; such attempts to take over high-quality habitat have been shown in several territorial species (Arcese et al 1992;Iguchi & Hino 1996). In social species, subordinate individuals can seriously harm breeder and group performance (Bourke & Franks 1995;Young & Clutton-Brock 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals are unlikely to remain passively assigned to poor habitat or status as long as there are no vacancies, as assumed by models of territorial species demography, or ideal despotic distribution (IDD; Fretwell & Lucas 1970). Instead, they may attempt to improve their breeding career actively; such attempts to take over high-quality habitat have been shown in several territorial species (Arcese et al 1992;Iguchi & Hino 1996). In social species, subordinate individuals can seriously harm breeder and group performance (Bourke & Franks 1995;Young & Clutton-Brock 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nest predation also reduces productivity in cowbird hosts, and parasitism and predation have been jointly linked to population declines in several species, including threatened and endangered neotropical migrants (3-9). This link is currently believed to be a coincidental result of the preferences of nest predators and cowbirds for fragmented habitats and ecological edges (10-15).In contrast, we have argued that cowbirds regularly depredate nests that are discovered too late in the host's nesting cycle to be suitable for parasitism, because this enhances future laying opportunities (16,17). Nest predation may also improve a cowbird's ability to synchronize its own laying with that of its host.…”
mentioning
confidence: 96%
“…Firstly, this study has shown that adult survival rate is low, but also extremely variable among years (Table 1). This variation may have dynamic effects on the social structure of the winter flock because the survival rate of adults may influence the rates of immigration and emigration, especially by juveniles (Arcese et al, 1992). For example, although there was a significant difference in adult survival rates between two winters (36 vs 17%, Table 1), overall flock size did not differ between the two winters, indicating possible density-dependent recruitment or immigration.…”
Section: Discussionmentioning
confidence: 99%